2017
DOI: 10.1089/jwh.2016.6099
|View full text |Cite
|
Sign up to set email alerts
|

High Initiation of Adjuvant Hormonal Therapy Among Uninsured Stages I–III Breast Cancer Patients Treated in a Safety-Net Healthcare System

Abstract: Safety-net healthcare systems providing access to AHT (i.e., through reduced copays) could improve the number of eligible patients initiating therapy. Continuity and integration of care in these settings may reduce disparities frequently observed in uninsured, low-income breast cancer populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The comparatively small effect magnitude of clinical and neuroimaging follow‐up visits on these outcomes in comparison with an SNH setting could potentially be due to challenges in quantifying the quality of follow‐up, such as differentiating symptom‐triggered visits from routine visits, accounting for differences in clinical follow‐up visits due to varying systemic therapy regimens, and determining whether patients received care at institutions outside our health care network . Nonetheless, our results suggest that there may be other unaccounted‐for risk factors associated with an SNH practice setting, such as more patient comorbidities, less access to and compliance with systemic therapies, fewer hospital resources, and a lower quality of medical care …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The comparatively small effect magnitude of clinical and neuroimaging follow‐up visits on these outcomes in comparison with an SNH setting could potentially be due to challenges in quantifying the quality of follow‐up, such as differentiating symptom‐triggered visits from routine visits, accounting for differences in clinical follow‐up visits due to varying systemic therapy regimens, and determining whether patients received care at institutions outside our health care network . Nonetheless, our results suggest that there may be other unaccounted‐for risk factors associated with an SNH practice setting, such as more patient comorbidities, less access to and compliance with systemic therapies, fewer hospital resources, and a lower quality of medical care …”
Section: Discussionmentioning
confidence: 88%
“…22 Nonetheless, our results suggest that there may be other unaccounted-for risk factors associated with an SNH practice setting, such as more patient comorbidities, less access to and compliance with systemic therapies, fewer hospital resources, and a lower quality of medical care. [23][24][25][26] There are numerous possible explanations for the disparity in the number of neuroimaging follow-up visits at the 2 hospitals, including differences in age, race, income, education, language, social supports, distance from the treatment center, access to transportation, ability to take time off from work, and severity of disease. 23 The fact that SNH patients still received similar clinical follow-up suggests that the underlying reasons are either specific to neuroimaging or affect compliance with neuroimaging studies more than clinical visits.…”
Section: Discussionmentioning
confidence: 99%
“…A 2004 Massachusetts Health Insurance Survey found that over 90% of newly enrolled Medicaid enrollees after Massachusetts health reform were previously unenrolled [ 35 ]. Previous studies have demonstrated that higher out of pocket prescription drug costs are associated with lower initiation and higher discontinuation of medications and treatments [ 27 , 31 , 32 , 40 – 44 ]. Our study further supports these findings, estimating about a 5-percentage point relative increase in the likelihood of BCA patients aged 20–64 years in low-income areas initiating AET after reform relative to BCA patients in the same age group living in high-income areas.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that endocrine therapy is recommended for all patients with HR+ disease, regardless of disease characteristics, the endocrine treatment rate (68.9%) for women with early stage disease was lower than expected [30][31][32]. Other real-world reports have noted similar or higher rates of adjuvant endocrine therapy usage (70-86%), with some highlighting challenges related to adherence and duration of treatment [27,[33][34][35][36][37][38][39][40][41]. Unfortunately, an analysis of factors influencing treatment was beyond the scope of our research, but is warranted in order to optimize outcomes [42] in patients with this subtype of BC.…”
Section: Treatmentmentioning
confidence: 92%